Pegasta sova Tyto alba v JV delu Prekmurja - Katalinič, Dane (Acrocephalus, 2000)
During 1995-1999, three localities where regular presence of Barn Owls was established were discovered in the SE part of Prekmurje covering some 225 km2.The owls inhabit the abandoned state cowsheds.
Keywords: bird; Birds; ptice; Ecosystem; ornitologija; sove; Prekmurje